2015
DOI: 10.1136/bmj.h3658
|View full text |Cite
|
Sign up to set email alerts
|

How to use biologic agents in patients with rheumatoid arthritis who have comorbid disease

Abstract: Although biologic disease modifying anti-rheumatic drugs (bDMARDs) have improved the quality of life of patients with rheumatoid arthritis, side effects remain a problem, especially for patients with pre-existing comorbidities. Randomized controlled trials of such drugs in rheumatoid arthritis typically exclude patients with comorbidities and are of short duration, so they do not provide data on adverse events in these people. Other data sources such as national bDMARD registries are limited by the preselectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 152 publications
(131 reference statements)
0
5
0
3
Order By: Relevance
“…Guidelines for RA invite physicians to include comorbidities in treatment decisions [ 2 , 18 ]. We found that an increase in the number of comorbidities resulted in a decreased preference for adding TNFi and TCZ, and an increased preference for ABA and RTX, as well as for the csDMARD-based strategies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Guidelines for RA invite physicians to include comorbidities in treatment decisions [ 2 , 18 ]. We found that an increase in the number of comorbidities resulted in a decreased preference for adding TNFi and TCZ, and an increased preference for ABA and RTX, as well as for the csDMARD-based strategies.…”
Section: Discussionmentioning
confidence: 99%
“…The three poor prognostic factors have been consistently used for guiding treatment decisions in RA, namely disease activity according to Disease Activity Score in 28 Joints (DAS28), presence of structural damage, and presence of autoantibodies [ 2 , 3 ]. The selected comorbidities were chosen as variables of interest because of their frequency in patients with RA [ 18 ]. None of the comorbidities were associated with an absolute or relative contraindication for any therapeutic option.…”
Section: Methodsmentioning
confidence: 99%
“…Несомненное клиническое значение имеют рекомендации, касающиеся ведения пациентов с некоторыми сопутствующими заболеваниями (инфекция вирусом гепатита В и С, сердечная недостаточность, злокачественные новообразования). Однако уровень их доказательности невысок, и многие проблемы безопасного лечения пациентов с коморбидными заболеваниями, в первую очередь с кардиоваскулярной патологией, требуют дальнейшего изучения [74,75] и будут более подробно обсуждены в сле-дующих лекциях программы последипломного обучения ревматологов.…”
Section: таблицаunclassified
“…По имеющимся данным, наиболее клинически значи-мыми формами коморбидности являются кардиоваскуляр-ная патология, остеопороз, ИЗЛ, инфекционные осложне-ния, злокачественные новообразования, недомогание, де-прессия, когнитивные расстройства [66]. Примечательно, что понимание важности коморбидных заболеваний как фактора, затрудняющего гармонизацию лечения пациен-тов, послужило основанием для разработки мультидисци-плинарных рекомендаций [73][74][75], касающихся ведения «полиморбидных» пациентов с РА (а также с псориазом О р и г и н а л ь н ы е и с с л е д о в а н и я…”
Section: таблицаunclassified